Experimental investigation of self-healing properties in silicone rubber and epoxy resin - Mohd. Sholihin Ismail, 1990-, author; Yanuar Zulardiansyah Arief, supervisor; Fakulti Kejuruteraan Elektrik (2013)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2013